1990
DOI: 10.1159/000461169
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and Severe Reactions during Autologous Blood Donations Are No More Frequent than during Homologous Blood Donations

Abstract: Because autologous donation is permitted for donors who do not meet homologous blood donation standards, referring physicians and blood center personnel may be concerned about autologous donor reactions. Small studies have determined that mild reactions do not occur more frequently, but the incidence of rarer, more serious, moderate and severe reactions is unknown. We therefore studied the frequency of reactions during 10,200 autologous and 219,307 concurrent homologous donations at four blood centers. No sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
3
8
1
Order By: Relevance
“…Therefore, in our study VVR are only rated as mild AE (grade II). The overall rate of AE in our analysis was 2.08% with respect to the number of patients studied and 1.17% for the number of donations performed; this rate of AE is within the same order of magnitude as those reported in the multicenter studies mentioned above [8][9][10]. In agreement with the data of AuBuchon et al [9], all severe and one fatal AE were found in patients with clinically relevant co-existing diseases (ASA score III) which would definitely exclude patients from allogeneic blood donation; and also in agreement with the data of AuBuchon et al [9], all severe and one fatal outcome are of cardio-and/or cerebrovascular nature.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, in our study VVR are only rated as mild AE (grade II). The overall rate of AE in our analysis was 2.08% with respect to the number of patients studied and 1.17% for the number of donations performed; this rate of AE is within the same order of magnitude as those reported in the multicenter studies mentioned above [8][9][10]. In agreement with the data of AuBuchon et al [9], all severe and one fatal AE were found in patients with clinically relevant co-existing diseases (ASA score III) which would definitely exclude patients from allogeneic blood donation; and also in agreement with the data of AuBuchon et al [9], all severe and one fatal outcome are of cardio-and/or cerebrovascular nature.…”
Section: Resultssupporting
confidence: 83%
“…So far, comparable data with respect to the number of patients studied have only been reported in three multicenter studies [8][9][10]. By comparing 10,200 autologous with 219,307 allogeneic donations, McVay et al [8] did not prove statistically significant differences in AE between autologous and allogeneic donors, neither for mild AE (2.26 versus 2.26%), nor for moderate AE (0.19 versus 0.22%) nor for severe complications (0.039 versus 0.037%). Table 6.…”
Section: Discussionmentioning
confidence: 94%
“…As long as these conditions are respected, the rate of mild and moderate reactions is not higher for autologous blood collection than for allogeneic blood donation. This has previously been shown in different settings [13,14], but the variability in reporting problems at different blood centers was very high [15], resulting in reaction rates between 1 and 8% for comparable patient groups. Severe reactions, defined as those requiring hospitalization, were found in 1 of 16,783 autologous blood donations and hence 12 times more frequently than in allogeneic donors [16].…”
Section: Resultssupporting
confidence: 61%
“…Comparison between donors who experienced adverse events and normal donors erogeneity [1,2,[4][5][6][7][8][9][10][11]. Furthermore, most reports come from multicenter studies with a marked center-to-center variation in adverse events rates [1,2,14,15,19]. Our single-center study should overcome this limitation and allow a homogeneous collection of data.…”
Section: Discussionmentioning
confidence: 99%